2018
DOI: 10.1108/ics-05-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cyberattacks on stock performance: a comparative study

Abstract: The recent spate of cyberattacks against critical infrastructure systems have necessitated the quest to examine the impact of such events on stock values. The question is 'what is the impact of cyberattack on stock values'? To address the question, data on cyberattacks announcements from 96 firms that are listed on S&P 500 1 between January 03, 2013 and December 29, 2017 were reviewed to draw some conclusions. The empirical analysis was performed in two ways: cross-section and industry level. The study employs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…To study the special influence of a range of incidents, from corporate purchases to joint venture establishment to CEO progressions the method of 'event study' has been engaged comprehensively in the accounting, finance and information security literature (Bose & Leung, 2013;Cavusoglu et al, 2004;Hovav et al, 2017;Kannan et al, 2007;Rosati et al, 2017;Smith et al, 2018;Tweneboah-Kodua et al, 2018;Yayla & Hu, 2011). This statistical practise advocates that an unanticipated event is probable to influence (increase or decrease) the script price resulting an abnormal returns on script prices (MacKinlay, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the special influence of a range of incidents, from corporate purchases to joint venture establishment to CEO progressions the method of 'event study' has been engaged comprehensively in the accounting, finance and information security literature (Bose & Leung, 2013;Cavusoglu et al, 2004;Hovav et al, 2017;Kannan et al, 2007;Rosati et al, 2017;Smith et al, 2018;Tweneboah-Kodua et al, 2018;Yayla & Hu, 2011). This statistical practise advocates that an unanticipated event is probable to influence (increase or decrease) the script price resulting an abnormal returns on script prices (MacKinlay, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…While intangible costs are difficult to estimate, such as loss of trust, reputation, and confidence by business stakeholders for future transactions. Underpinned by the Efficient Market Hypothesis in its semi-strong form (Fama, 1991;Fama et al, 1969;Malkiel & Fama, 1970) researches have tried to examine the impact of IS breach announcements on stock prices for effected firms (Berkman et al, 2018;Bianchi & Tosun, 2018;Campbell et al, 2003;Cavusoglu et al, 2004;Ettredge & Richardson, 2001;Hovav & D'Arcy, 2004;Kannan et al, 2007;Malhotra & Kubowicz Malhotra, 2011;Pirounias et al, 2014;Sangvinatsos, 2017;Sinanaj & Muntermann, 2013;Smith et al, 2018;Tweneboah-Kodua et al, 2018). Most of these studies have concluded a negative impact on stock price by considering the effect of un-systematic risk factors surrounding the breach such as factors specific to that type of attack (Arcuri et al, 2017;Bose & Leung, 2014;Hovav & D'Arcy, 2003), type of firm (Cavusoglu et al, 2004;Goel & Shawky, 2009;Rosati et al, 2017) and type of industry (Pirounias et al, 2014;Yayla & Hu, 2011) as shown in Figure 01.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to verify whether the results of research carried out on other sectors (Goel and Shawky, 2009) are confirmed for hospitality. In fact, literature has shown that the cumulative effects of cyber attacks on listed companies’ prices can be more informative if the data are grouped by economic sector (Tweneboah-Kodua et al , 2018). This is particularly relevant for the hospitality industry, where the risk of a cyber attack is not firm-specific, but it has a potentially systemic nature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stealing Personally Identifiable Information (PII) contributes to more than 50% of all data breaches and has a significant effect on revenue and stock markets within the retail sector unlike other sectors. A lot of breaches are usually discovered way later after the attack has happened [48]. Article 31 of the GDPR requires Data Controllers to report data breaches to the supervisory authority within 72 hours of becoming aware of the breach.…”
Section: Data Breachesmentioning
confidence: 99%
“…In order to conform with the of Data Minimization where data collected is required to perform a specific purpose [13], tracking cookies which are essential in performing analytics is not possible. Data analytics is one of the major contributors of revenue streams for digital retailers [48]. This is a major challenge to digital retailers.…”
Section: Predicting Shopping Behaviors Of Existing Customersmentioning
confidence: 99%